Angiotensin Converting Enzyme Inhibitors (ACEIs) Decrease the Progression of Cardiac Fibrosis in Rheumatic Heart Disease Through the Inhibition of IL-33/sST2 - Ambari, Ade M.; Setianto, Budhi; Santoso, Anwar; Radi, Basuni; Dwiputra, Bambang; Susilowati, Eliana; Tulrahmi, Fadilla; Doevendans, Pieter A.; Cramer, Maarten J. (Frontiers in Cardiovascular Medicine, 2020)
Rheumatic heart disease (RHD) is still prominent in developing countries and pose a big medical challenge and burden. Pathogenesis of RHD is influenced by the triad of host, agent and environment. Autoantigens generated from Group A Streptococcus (GAS) infection are captured by the resident dendritic cells (DCs) in heart valvular endothelium. DCs then differentiates into antigen presenting cell (APC) in the valve interstices. APC induce the activation of autoreactive T cells. These successive cascades lead to an increase in inflammation and tissue fibrosis. Cardiac fibrosis is promoted through the activation of Mitogen activated protein kinase (MAPK) pathway and its downstream signaling that involves the binding of transforming growth factor-β (TGF-β) to its receptor followed by the phosphorylation of Smad2, Smad2 complexes with Smad3 and Smad4 and translocates into the nucleus. Angiotensin II enhances the migration, maturation, and the presenting capability of DCs. In RHD, Angiotensin II induces fibrosis via the stimulation of TGF-β, which further increase the binding of IL-33 to sST2 but not ST2L, resulting in the upregulation of Angiotensin II and progression of cardiac fibrosis. This cascade of inflammation and valvular fibrosis cause calcification and stiffening of the heart valves in RHD. Angiotensin converting enzyme inhibitors (ACEIs) inhibit Angiotensin II production, which in turn decreases TGF-β expression and the onset of overt inflammatory response. This condition leads to the reduction in the sST2 as the decoy receptor to ‘steal’ IL-33, and IL-33 binds to the ST2L and results in cardioprotection against cardiac fibrosis in the pathogenesis of RHD.